Prevalence and Severity of Categorical and Dimensional Personality Disorders in Adolescents with Eating Disorders. (14th November 2013) - Magallón‐Neri, Ernesto; González, Esther; Canalda, Gloria; Forns, Maria; De La Fuente, J. Eugenio; Martínez, Estebán; García, Raquel; Lara, Anais; Vallès, Antoni; Castro‐Fornieles, Josefina
Abstract Objective The objective of this study is to explore and compare the prevalence of categorical and dimensional personality disorders (PDs) and their severity in Spanish adolescents with Eating Disorders (EDs). Method Diagnostic and Statistical Manual of Mental Disorders Fourth Edition and International Classification of Diseases, Tenth Revision‐10 modules of the International Personality Disorder Examination were administered to a sample of 100 female adolescents with EDs (mean age = 15.8 years, SD = 0.9). Results Thirty‐three per cent of the sample had at least one PD, in most cases a simple PD. The rate of PDs was 64–28% in anorexia and 25% in EDs not otherwise specified. The highest dimensional scores were observed in bulimia, mainly in borderline and histrionic PDs, and higher scores for anankastic PD in anorexia than in the other ED diagnoses. Overall, purging type EDs had higher cluster B personality pathology scores than restrictive type. Discussion Adolescent female patients with ED have a risk of presenting a comorbid PD, especially patients with bulimia and purging type EDs. Copyright © 2013 John Wiley & Sons, Ltd and Eating Disorders Association.